2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7590798
|View full text |Cite
|
Sign up to set email alerts
|

Novel measure of the weigh distribution balance on the brain network: Graph complexity applied to schizophrenia

Abstract: Abstract-The aim of this study was to assess brain complexity dynamics in schizophrenia (SCH) patients during an auditory oddball task. For that task, we applied a novel graph measure based on the balance of the node weighs distribution. Previous studies applied complexity parameters that were strongly dependent on network topology. This fact could bias the results besides being necessary correction techniques as surrogating process. In the present study, we applied a novel graph complexity measure from the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…In this regard, phase synchronization was suggested as a key mechanism of dynamical neuronal communication, and can provide a useful measure of neural integration in sensory task-relevant procedures [47]. These findings are consistent with another study that showed greater differences between controls and SCH patients in the assessment of the evoked response than in the evaluation of the total response (induced and evoked) in delta band [32]. Therefore, the significant reduction of the irregularity in the evoked response for controls and the less evident difference in the evoked response for SCH patients reveals that activation response is weakly phase-locked to stimulus in schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In this regard, phase synchronization was suggested as a key mechanism of dynamical neuronal communication, and can provide a useful measure of neural integration in sensory task-relevant procedures [47]. These findings are consistent with another study that showed greater differences between controls and SCH patients in the assessment of the evoked response than in the evaluation of the total response (induced and evoked) in delta band [32]. Therefore, the significant reduction of the irregularity in the evoked response for controls and the less evident difference in the evoked response for SCH patients reveals that activation response is weakly phase-locked to stimulus in schizophrenia.…”
Section: Discussionsupporting
confidence: 81%
“…Low frequencies, like alpha band, are related to long-range interactions [20], suggesting that impaired activation response of long-range interactions might contribute to the pathological process. The lower irregularity reduction in the cognitive response of SCH patients seems to be associated with an abnormal information processing, as well as it could be related to the disrupted integrative functions of local and distributed neural circuits [32]. This result suggests that SCH is accompanied by a disrupted network reorganization of neural functions responsible of the P300 generation, mainly in long-range interaction.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations